Handbook of Innovation & Appropriate Technologies for International De velopment (Handbook of Innovation & Appropriate Technologies for International De velopment, 2022)
"Handbook of Innovation & Appropriate Technologies for International D evelopment" published on 20 Oct 2022 by Edward Elgar Publishing.